2010
DOI: 10.1007/s11242-010-9645-1
|View full text |Cite
|
Sign up to set email alerts
|

Injection, Flow, and Mixing of CO2 in Porous Media with Residual Gas

Abstract: Geologic structures associated with depleted natural gas reservoirs are desirable targets for geologic carbon sequestration (GCS) as evidenced by numerous pilot and industrial-scale GCS projects in these environments world-wide. One feature of these GCS targets that may affect injection is the presence of residual CH 4 . It is well known that CH 4 drastically alters supercritical CO 2 density and viscosity. Furthermore, residual gas of any kind affects the relative permeability of the liquid and gas phases, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…These features add significant complexity when approximating the natural system, and challenges arise in dealing with boundary conditions. In addition, presence of methane has been confirmed in the brine, which can potentially exsolve and impact pressure buildup history and CO 2 plume extent (Oldenburg and Doughty, 2011).…”
Section: The S-3 Sitementioning
confidence: 94%
“…These features add significant complexity when approximating the natural system, and challenges arise in dealing with boundary conditions. In addition, presence of methane has been confirmed in the brine, which can potentially exsolve and impact pressure buildup history and CO 2 plume extent (Oldenburg and Doughty, 2011).…”
Section: The S-3 Sitementioning
confidence: 94%
“…As was shown in the previous section, numerical simulations of CO 2 injection into a reservoir containing CH 4 predict the accumulation of a CH 4 bank at the head of the CO 2 plume (Oldenburg and Doughty 2011;Battistelli and Marcolini 2009;Taggart 2010). The system in discussion can be differentiated into three regions (Hosseini et al 2012).…”
Section: Effect Of Initial Gas Saturationmentioning
confidence: 84%
“…The development of the CH 4 bank ahead of the CO 2 has been explained as follows (Taggart 2010;Oldenburg and Doughty 2011;Hosseini et al 2012). As CO 2 is injected, it partitions into the gas phase and the aqueous phase.…”
Section: Effect Of Initial Gas Saturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Blanco et al (2012) reported CH 4 levels as high as 6% in industrial emissions in Spain (generated by waste management); however, a study conducted by de Visser et al (2008), in agreement with the European Enhanced Capture (ENCAP) project, suggested a limit of 4% CH 4 in gas injection streams. CH 4 can also be present as a native gas prior to injection (Taggart, 2010;Oldenburg and Doughty, 2011;Hosseini et al, 2012). The production of methane by methane-producing bacteria is also a source of CH 4 within storage reservoirs (Leu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%